The Influence of Organizational Commitment and Organizational Culture on Teacher Performance with Job Satisfaction as a Moderating Variable at SDN 5 Bathin Salopan - Adisman, Adisman; Rahmawati, Rahmawati (Dinasti International Journal of Digital Business Management, 2023)
Good teacher performance is always a requirement for school principals where they dedicate themselves. Many factors can influence teacher performance, but this research only aims to see and analyze: 1) the influence of organizational commitment on job satisfaction; 2) the influence of organizational culture on job satisfaction; 3) the influence of satisfaction on teacher performance; 4) the direct influence of commitment on teacher performance; 5) the direct influence of organizational culture on teacher performance; 6) the indirect effect of organizational commitment on teacher performance with motivation as a moderating variable; 7) indirect influence of organizational culture on teacher performance with motivation as a moderating variable. This research was conducted at SDN 5 Bathin Solapan using 21 teachers as samples. This research data consists of primary and secondary data obtained using questionnaires, research files, observations and interviews. Data analysis and hypothesis testing were carried out using the Structural Equatin Modeling (SEM) model and data processing was carried out with the SmartPLS program and hypothesis testing was carried out with an alpha of 5%. The results of this research conclude that: 1) it is true that there is a significant influence of the organizational commitment variable on job satisfaction; 2) it has been proven that there is a significant influence of organizational culture on job satisfaction; 3) it is proven that there is a significant influence of satisfaction on teacher performance; 4) there is no proven direct influence of commitment on teacher performance; 5) it is proven that there is a direct significant influence of organizational culture variables on teacher performance; 6) it is proven that there is a significant indirect effect of the organizational commitment variable on teacher performance with motivation as a moderating variable; 7) it is proven that there is a significant indirect effect of organizational culture on teacher performance with motivation as a moderating variable.